The Fairclough Critical Discourse Analysis Model in the Used Motorcycle Sale Advertising on Facebook: A Case Study - Kusumaningsih, Dewi; Nugroho, Adit; Saptomo, Sri Wahono; Hadi, Saptono; Sudiatmi, Titik; Muryati, Sri (Edukasi, 2023)
This article examines the use of the Fairclough Model of Critical Discourse Analysis to strengthen the context of the advertisement discourse for used motorcycles sales on Facebook. Case studies were conducted at Ninja R/Rr Sales and Purchases Group for the Klaten, Yogyakarta, Solo, and surrounding areas. This research aims to signify the use of Critical Discourse Analysis to strengthen the advertising discourse. The study implements a qualitative descriptive method with critical discourse analysis technique. The data were collected from the sales advertisements of used motorbikes posted on Ninja R/Rr Sales and Purchases Group for the Klaten, Jogja, Solo, and surrounding areas. The data were analyzed using the three dimensions of Critical Discourse Analysis of the Fairclough Model, consisting of the textual dimension, the discursive dimension, and the social dimension. The results highlight three viewpoints. In the textual dimension, the advertisements offer a clear and easy-to-understand structure. In the discursive dimension, the advertisements construct appropriate meanings contextually. In the social dimension, the advertisements represent social values related to the ownership of used motorbikes.